Pemanfaatan Limbah Cangkang Kerang Kijing (Pilsbryoconcha Exilis) Sebagai Katalisatator Pada Proses Carburizing - Hakim, Lukman; Ramli, Ramli; Sugiyarto, Sugiyarto (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Indonesia's natural products are very rich, including containing several types of animals, one of which is a clam that belongs to one type of shellfish. Mussel shells contain 39.55% calcium carbonate (CaCO3). The presence of calcium carbonate in the shell makes it possible to use it as a source of catalyst in the carburization process. Carburization adds carbon to the steel when heated to austenitic temperatures, causing the carbon to diffuse onto the steel surface. Low carbon steels with a carbon content of less than 0.3% are usually used in this process. Among the low-carbon steels widely used in industry, there is St 42 Steel, which has exceptional strength. Coconut shell charcoal is used as a catalyst. Coconut shell charcoal is one of the active carbon materials. Activated charcoal from coconut shell has low ash content, high reactivity and good solubility in water. The research method used is experimental. Steel ST 42 is used as the material. At the same time, the carburizing medium is activated carbon powder from coconut shell and shellfish powder by 10%, 20% and 30%, respectively, when heated for 3.6 and 9 hours.